Ethanolic Extract of Red Okra Pods Induces Aberrant Spindle Segregation and Apoptotic Cell Death by Disrupting the Wnt Signaling Pathway in Colon Cancer Cells - Firli Rahmah Primula Dewi; Sri Puji Astuti Wahyuningsih; Vuanghao Lim; Lionel Lian Aun In; Alfiah Hayati (Iranian Journal of Medical Sciences)
Background: In approximately 80% of colorectal cancer cases, mutations in the adenomatous polyposis coli (APC) gene disrupt the Wingless-related integration site (Wnt)/β-catenin signaling pathway, a crucial factor in carcinogenesis. This disruption may result in consequences such as aberrant spindle segregation and mitotic catastrophe. This study aimed to analyze the effectiveness of the ethanolic extract of red okra (Abelmoschus esculentus) pods (EEROP) in inducing apoptosis in colorectal cancer cells (SW480) by inhibiting the Wnt/β-catenin signaling pathway.Methods: The IC50 of EEROP in SW480 cells was determined by treating the cells with varying doses of EEROP, ranging from 0 to 1000 µg/mL. Apoptosis assay and signaling pathway analysis were performed through immunofluorescence staining and Western Blotting on SW480 cells treated with 250 µg/mL of EEROP for 72 hours. Results: EEROP treatment induced apoptosis in SW480 cells, marked by elevated levels of active caspase-3 (P<0.001) and cleaved poly-(ADP-ribose) polymerase (PARP)-1. Moreover, it notably decreased β-catenin protein levels, resulting in an augmented occurrence of cells displaying abnormal spindle segregation during mitosis (P=0.04).Conclusion: EEROP treatment reduces β-catenin protein levels, promotes abnormal spindle apparatus segregation, and finally leads to apoptotic cell death in CRC cells.